2020
DOI: 10.3390/cells9081861
|View full text |Cite
|
Sign up to set email alerts
|

Clock Protein Bmal1 and Nrf2 Cooperatively Control Aging or Oxidative Response and Redox Homeostasis by Regulating Rhythmic Expression of Prdx6

Abstract: Many disorders of aging, including blinding-diseases, are associated with deficiency of brain and muscle arnt-like protein 1 (Bmal1) and, thereby, dysregulation of antioxidant-defense pathway. However, knowledge is limited regarding the role of Bmal1 regulation of antioxidant-pathway in the eye lens/lens epithelial cells (LECs) at the molecular level. We found that, in aging human (h)LECs, a progressive decline of nuclear factor erythroid 2-related factor 2 (Nrf2)/ARE (antioxidant response element)-mediated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 95 publications
(218 reference statements)
1
61
0
Order By: Relevance
“…More recently, time-of-day-dependent regulation of Nrf-2 has been reported, which takes an important role for antioxidants [ 36 , 52 , 53 ]. Chhunchha et al reported that the molecular Bmal1 controls the inflammatory response through regulating Nrf-2 in innate immune cells [ 54 ]. Mahajan et al found that Bmal1 and Nrf-2 cooperatively control oxidative response and redox homeostasis by regulating the rhythmic expression of Prx [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, time-of-day-dependent regulation of Nrf-2 has been reported, which takes an important role for antioxidants [ 36 , 52 , 53 ]. Chhunchha et al reported that the molecular Bmal1 controls the inflammatory response through regulating Nrf-2 in innate immune cells [ 54 ]. Mahajan et al found that Bmal1 and Nrf-2 cooperatively control oxidative response and redox homeostasis by regulating the rhythmic expression of Prx [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tryptophan-derived hormone melatonin—often viewed as a nutraceutical insomuch as it can be administered orally and is sold in capsule form over-the-counter—has phase 2 activity that appears to reflect up-regulation of nrf2 at the transcriptional level [ 86 , 87 , 88 ]. This may reflect the fact that the promoter of the nrf2 gene contains E boxes that bind the “clock” transcription factor Bmal1, in conjunction with the protein Clock, and this drives nrf2 transcription [ 89 , 90 ]. The expression of Bmal1 and other so-called clock genes varies with a diurnal rhythm in many types of cells; a nocturnal surge of melatonin produced by the pineal gland somehow functions to coordinate this diurnal variation with light/dark cycles [ 91 , 92 ].…”
Section: Nlrp3 Inflammasome Suppression Via Phase 2 Inductionmentioning
confidence: 99%
“…The neurohormone melatonin (MLT), secreted nocturnally by the pineal gland as a synchronizer of diurnal biological rhythms, is known to have this property [ 54 ]. This might reflect increased activity of the fundamental clock protein Bmal1, one of whose transcriptional targets is Nrf2 [ 55 , 56 , 57 ]. MLT administration has been found to benefit cognitive function, lessen tau phosphorylation, and decrease amyloid β levels in multiple models of AD in mice, albeit it is unclear to what extent antioxidant effects mediate these benefits [ 58 , 59 , 60 , 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%